A STUDY OF WORK PLACE DEVIANCES WITH RESPECT TO AGE AND GENDER (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Workplace deviances have always been critical  issues in organization among researchers and  managers. The occurrence of deviant behavior  involves deception, employees thievery (stealing  & shoplifting), squashing, unexcused absences,  taking long breaks, rude violent behavior, and  sexual abuses at the workplace accounts a big  task for organizations. The impact of these  behaviors is enormous on organization and  individual & such behavior incur massive  economic loss. To make organization productive  & effective, we need to work hard to get over  with this problem and bring harmony among  them and in the organization. Keeping in mind  the present study aims to study workplace  deviant behavior in private sector among the  working professionals. A sample of 60 working  professional were taken from private sector  undertaking and tested on the two aspects of  workplace deviances ie., interpersonal deviances  and organizational deviances. The aim of this  paper is to study the impact of age and gender  on workplace deviances. The age & gender has  shown significant relation with interpersonal  deviances than organizational deviances.
Keywords: Workplace deviances; organizational deviances; Interpersonal deviances; age and gender